THE APPLICATION OF GREEN ACCOUNTING ON STOCK ACTIVITYIN ISLAMIC PRESPECTIVE - Weny Rosilawati; Heni Noviarita; Nur Wahyu Ningsih; Chandra Prayoga (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2021)
Environmental accounting is applied by several companies to produce quantitative assessments of the cost and impacts of environmental protection. Social and environmental disclosures have  an influence on stock prices and inventors will choose stocks in companies that provide high returns. This research is quantitative in nature. The population of this study is the Corporate Social Responsibility (CSR) report and the financial statements of mining companies listed on the ISSI for the 2014-2018 period. Based on the purposive sampling method a sample of 7 mining companies was obtained. The data analysis method used simple linear regression analysis. The result of this study are the application of accounting in social and environmental disclosures has a positive effect on stock reactions, and in an Islamic perspective it is in accordance with the concept of sharia enterprise theory in benefit and responsibility. Corporate social responsibility is responsibility for the overall relationship between the company and its stakeholders. These relationships include consumers, employees, communities, owners / investors, government, and suppliers. The current understanding of social responsibility provides guidance that a company is no longer an entity that is only selfish but an entity that must adapt to its culture and its social environment. This is what Allah warned in QS. Ar-Rum, Verse 41 which in this case explains that Allah SWT commands humans to always protect their surroundings.